Early brain-body impact of emotional arousal - D'Hondt, Fabien; Lassonde, Maryse; Collignon, Olivier; Dubarry, Anne-Sophie; Robert, Manon; Rigoulot, Simon; Honoré, Jacques; Lepore, Franco; Sequeira, Henrique (Frontiers in Human Neuroscience, 2010)
Current research in affective neuroscience suggests that the emotional content of visual stimuli activates brain–body responses that could be critical to general health and physical disease. The aim of this study was to develop an integrated neurophysiological approach linking central and peripheral markers of nervous activity during the presentation of natural scenes in order to determine the temporal stages of brain processing related to the bodily impact of emotions. More specifically, whole head magnetoencephalogram (MEG) data and skin conductance response (SCR), a reliable autonomic marker of central activation, were recorded in healthy volunteers during the presentation of emotional (unpleasant and pleasant) and neutral pictures selected from the International Affective Picture System (IAPS). Analyses of event-related magnetic fields (ERFs) revealed greater activity at 180 ms in an occipitotemporal component for emotional pictures than for neutral counterparts. More importantly, these early effects of emotional arousal on cerebral activity were significantly correlated with later increases in SCR magnitude. For the first time, a neuromagnetic cortical component linked to a well-documented marker of bodily arousal expression of emotion, namely, the skin conductance response, was identified and located. This finding sheds light on the time course of the brain–body interaction with emotional arousal and provides new insights into the neural bases of complex and reciprocal mind–body links.